An approach for teaching automatic control in a laboratory of mechatronics - Padula, Fabrizio; Visioli, A. (2013)
In this paper we propose an approach to effectively teach the automatic control topic in a Laboratory of Mechatronics course. In particular, we propose to use a motion system with an elastic transmission in order to implement a motion control task. The use of this experimental setup, which includes both a mechanical and an electrical/electronic part allows the student to verify the importance of many concepts learned in previous courses such as PID control, cascade control, anti-windup, observer design, digital control. © IFAC.